2008
DOI: 10.4049/jimmunol.180.10.6768
|View full text |Cite
|
Sign up to set email alerts
|

Ly49H+ NK Cells Migrate to and Protect Splenic White Pulp Stroma from Murine Cytomegalovirus Infection

Abstract: In this study, we show that in the absence of a protective NK cell response, murine CMV causes destruction of splenic white and red pulp pulp areas in the first few days of infection. Destruction of T zone stroma is associated with almost complete loss of dendritic cells and T cells. We provide evidence that the virus replicates in red and white pulp stroma in vivo and in vitro. Control of white pulp viral replication is associated with migration of murine CMV-specific activated NK cells to white pulp areas, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
1
2

Year Published

2008
2008
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 31 publications
2
62
1
2
Order By: Relevance
“…Collectively, these results indicate that relatively lower MTHFR levels are associated with an enhanced control of acute MCMV infection. Uncontrolled MCMV replication is usually accompanied by massive production of pro-inflammatory cytokines, such as IFNa, IFNg and interleukin-12, and loss of spleen cell populations, which together contribute to MCMV-mediated pathology 23,24 In fact, detrimental effects of high levels of IFNa during viral infection have been observed 25,26 Abundant levels of IFNa can compromise host immune responses by inhibiting the differentiation of dendritic cells or by leading to CD8 þ T cell attrition 25,26 In contrast, MCMV-resistant mice showing low viral load present limited production of pro-inflammatory cytokines and increased specific subpopulations of spleen cells in comparison with susceptible mice 24,27 Thus, we monitored serum levels of IFNs at 1.5 days p.i., the peak of cytokine production and spleen cell numbers at 3 days p.i., the peak of cell loss. Mthfr À/À and Mthfr þ /À mice had lower cytokine levels than their wild-type counterparts even though the differences did not reach significance (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, these results indicate that relatively lower MTHFR levels are associated with an enhanced control of acute MCMV infection. Uncontrolled MCMV replication is usually accompanied by massive production of pro-inflammatory cytokines, such as IFNa, IFNg and interleukin-12, and loss of spleen cell populations, which together contribute to MCMV-mediated pathology 23,24 In fact, detrimental effects of high levels of IFNa during viral infection have been observed 25,26 Abundant levels of IFNa can compromise host immune responses by inhibiting the differentiation of dendritic cells or by leading to CD8 þ T cell attrition 25,26 In contrast, MCMV-resistant mice showing low viral load present limited production of pro-inflammatory cytokines and increased specific subpopulations of spleen cells in comparison with susceptible mice 24,27 Thus, we monitored serum levels of IFNs at 1.5 days p.i., the peak of cytokine production and spleen cell numbers at 3 days p.i., the peak of cell loss. Mthfr À/À and Mthfr þ /À mice had lower cytokine levels than their wild-type counterparts even though the differences did not reach significance (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported a transient migration of NK1.1 + cells [16], Ly49G2 + cells [17] or more recently Ly49H + cells [31] in the white pulp area of the spleen upon MCMV infection. These different reports were, however, limited by the specificity of the antibodies used or by the very low percentage of cells expressing the molecules that they recognized.…”
Section: Discussionmentioning
confidence: 99%
“…CD45.1 ϩ transferred cells were detected in situ after staining with anti-mouse CD45.1-FITC (eBioscience). Sample preparation for and analysis of quantitative real-time PCR was as previously described (14,19). Primer/probe sequences (ccl19, ccl21, cxcl13, ␤-actin) were published previously (14).…”
Section: Confocal Microscopy and Quantitative Real-time Pcrmentioning
confidence: 99%
“…Tissue preparation, staining, and image acquisition and analysis were performed as previously described (14,19). B cells were detected after staining with anti-mouse IgM conjugated to Rhodamine red (Jackson ImmunoResearch Laboratories) or anti-mouse B220 conjugated to Pacific blue (eBioscience).…”
Section: Confocal Microscopy and Quantitative Real-time Pcrmentioning
confidence: 99%